The origins of the 4 × 4 framework for noncommunicable disease at the World Health Organization. (March 2021) - Schwartz, Leah N.; Shaffer, Jonathan D.; Bukhman, Gene
Abstract: This paper traces the history of noncommunicable disease public health research and programming at the World Health Organization. Specifically, it investigates the origins of the now pervasive 4 × 4 framework focusing on four sets of diseases (cardiovascular diseases, diabetes, chronic respiratory diseases, and cancers) caused by four behavioral risk factors (tobacco use, harmful use of alcohol, unhealthy diets, and physical inactivity). We have found that the 4 × 4 framework developed as a generalization from strategies to control epidemics of cardiovascular disease and stroke in high-income countries during the second half of the twentieth century. These strategies, which were narrowly focused on interventions to address behavioral "lifestyle" risk factors as well as pharmacotherapy for physiologic risk factors, were ultimately packaged as an integrated approach initially in high-income countries and subsequently extended to low- and middle-income countries, where they have failed to address much of the burden among very poor populations. Highlights: The WHO has used the 4 × 4 framework as a dominant framing for NCDs and recommended interventions since at least 2011. The framework is based upon epidemiological research on risk factors for cardiovascular disease in high-income countries. The 4 × 4 framework has failed to effectively address the NCD burden in low- and middle-income countries.